Coherent Diffractive Imaging Using Table-top High Harmonic Generation - Dinh, Khuong Ba; Tran, Khoa Anh; Hannaford, Peter; Dao, Lap Van (Communications in Physics, 2018)
Coherent diffractive imaging (CDI) is a lensless microscopy technique in which the structure of a specimen of interest is probed using a coherent short-wavelength light source. CDI has been widely used in nanotechnology and structural biology to capture high resolution images of non-crystalline objects. In this paper, we review the theoretical and experimental aspects of coherent diffractive imaging using a focused narrow-bandwidth table-top high harmonic source. The review begins with an outline of generation and characterization of the high harmonic source. Theoretical description of coherent diffractive imaging technique is then summarized. The review concludes with our recent results in imaging using a single harmonic beam selected by employing XUV focusing mirrors. These achievements provide a promising technique for the non-crystallographic structural determination of membrane proteins using a table-top extreme ultraviolet source